Transforming Arabic Vocabulary Learning for Beginners through Interactive Digital Media - Yunanta, Iqbal Rozi (Nurul Jadid University, 2022)
Arabic vocabulary learning for beginners plays a crucial role in establishing a solid foundation for mastering the Arabic language and enhancing communicative competence. This study aims to analyze the effectiveness of interactive digital media in transforming Arabic vocabulary learning among beginner students. The background of this research lies in the growing need for innovative and engaging learning tools that align with the digital literacy of today's learners and can improve vocabulary retention and motivation. By integrating multimedia elements, interactive exercises, and instant feedback, digital media is considered capable of creating a more dynamic and learner-centered environment. This study uses a qualitative approach with descriptive methods, collecting data through classroom observations, interviews with teachers and students, and documentation of learning activities involving digital media. The findings reveal that interactive digital media significantly increases student engagement and motivation while enhancing vocabulary acquisition through multisensory stimulation and immediate reinforcement. Practically, this study suggests that the use of interactive digital platforms can accelerate the learning process, improve long-term vocabulary retention, and provide adaptive learning pathways for diverse learner needs. The implications highlight the potential of digital media as an effective pedagogical tool in modern Arabic language instruction, especially for beginner learners in formal educational settings.